The Arabidopsis Homolog of the Mammalian OS-9 Protein Plays a Key Role in the Endoplasmic Reticulum-Associated Degradation of Misfolded Receptor-Like Kinases - Su, Wei (Oxford University Press, 2012)
The endoplasmic reticulum-associated degradation (ERAD) is a highly conserved mechanism to remove misfolded membrane/secretory proteins from the endoplasmic reticulum (ER). While many of the individual components of the ERAD machinery are well characterized in yeast and mammals, our knowledge of a plant ERAD process is rather limited. Here, we report a functional study of an Arabidopsis homolog (AtOS9) of an ER luminal lectin Yos9 (OS-9 in mammals) that recognizes a unique asparagine-linked glycan on misfolded proteins. We discovered that AtOS9 is an ER-localized glycoprotein that is co-expressed with many known/predicted ER chaperones. A T-DNA insertional atos9-t mutation blocks the degradation of a structurally imperfect yet biochemically competent brassinosteroid (BR) receptor bri1-9, causing its increased accumulation in the ER and its consequent leakage to the cell surface responsible for restoring the BR sensitivity and suppressing the dwarfism of the bri1-9 mutant. In addition, we identified a missense mutation in AtOS9 in a recently discovered ERAD mutant ems-mutagenized bri1 suppressor 6 (ebs6-1). Moreover, we showed that atos9-t also inhibits the ERAD of bri1-5, another ER-retained BR receptor, and a misfolded EFR, a BRI1-like receptor for the bacterial translation elongation factor EF-Tu. Furthermore, we found that AtOS9 interacted biochemically and genetically with EBS5, an Arabidopsis homolog of the yeast Hrd3/mammalian Sel1L known to collaborate with Yos9/OS-9 to select ERAD clients. Taken together, our results demonstrated a functional role of AtOS9 in a plant ERAD process that degrades misfolded receptor-like kinases.